Search for biomarkers of asbestos exposure and asbestos-induced cancers in investigations of the immunological effects of asbestos - Hidenori Matsuzaki; Naoko Kumagai-Takei; Suni Lee; Megumi Maeda; Nagisa Sada; Tamayo Hatayama; Shoko Yamamoto; Miho Ikeda; Kei Yoshitome; Yu Min; Yasumitsu Nishimura; Takemi Otsuki (Komiyama Printing Co. Ltd, 2017)
Abstract The immunological effects of asbestos exposure on various lymphocytes such as the regulatory T cell (Treg), responder CD4+ T helper cell (Tresp), CD8+ cytotoxic T lymphocytes (CTL), and natural killer (NK) cells were investigated. Results show that asbestos exposure impairs antitumor immunity through enhancement of regulatory T cell function and volume, reduction of CXCR3 chemokine receptor in responder CD4+ T helper cells, and impairment of the killing activities of CD8+ cytotoxic T lymphocytes (CTL) and NK cells. These findings were used to explore biological markers associated with asbestos exposure and asbestos-induced cancers and suggested the usefulness of serum/plasma IL-10 and TGF-β, surface CXCR3 expression in Tresp, the secreting potential of IFN-γ in Tresp, intracellular perforin level in CTL, and surface expression NKp46 in NK cells. Although other unexplored cytokines in serum/plasma and molecules in these immunological cells, including Th17, should be investigated by experimental procedures in addition to a comprehensive analysis of screening methods, biomarkers based on immunological alterations may be helpful in clinical situations to screen the high-risk population exposed to asbestos and susceptible to asbestos-related cancers such as mesothelioma.